Beyond Literal Meaning: Developing EFL Learners’ Pragmatic Listening Competence through Authentic Audio Materials - Yessy Marzona; Herdi Herdi (Jurnal Ilmiah Langue and Parole, 2026)
Listening comprehension in English as a Foreign Language (EFL) learning is often associated with understanding explicit information, while learners’ ability to interpret speakers’ intended meanings in authentic communicative contexts receives comparatively less attention. This study investigates the development of EFL learners’ pragmatic listening competence through the use of authentic audio materials. Employing a quasi-experimental mixed-methods design, the study involves undergraduate EFL learners who are assigned to an experimental group receiving instruction through authentic audio materials and a control group receiving conventional listening instruction. The authentic materials include naturally occurring conversations, interviews, business-related interactions, and other context-rich spoken texts designed to expose learners to indirect meanings, speech acts, politeness strategies, implicatures, and contextual cues. Data are collected through a pragmatic listening comprehension test, a learner perception questionnaire, and semi-structured interviews. Quantitative data are analyzed using descriptive and inferential statistics, including paired-samples and independent-samples tests, while qualitative data are analyzed thematically. The study is expected to demonstrate that exposure to authentic audio materials can significantly enhance learners’ ability to interpret speaker intentions and implied meanings beyond literal comprehension. The findings are expected to contribute to the development of pragmatic-oriented listening pedagogy and provide empirical evidence for integrating authentic spoken materials into EFL listening instruction.